New Inscriptions from the Kayseri Museum I - Burak Takmer; Murat Arslan; Nihal Tüner Önen (Gephyra, 2006)
New Inscriptions from the Kayseri Museum IThis paper presents 13 new funerary inscriptions from the Kayseri Museum. With the exception of stele no. 1, which is from Comana, their origins are not recorded in the inventory lists of the museum. Most of them were probably found in and around Caesarea, the capital of the province of Cappadocia. According to the letter forms most stelai are from 3th century AD. All of them feature funerary inscriptions with new onomastic information. The stele no. 1 sheds new light on two problematic Anatolian names â€” Koleis and Tilleis. A large number of the names mentioned on the stelai are of Greek origin. Apollonios in no. 2 is called “the first among the Hellenes”. His obvious belief in the Greekpaideia is also apparent from the names of his former slaves. He called them after famous politicians like Alkibiades and Dion known from Plato and after authors like Ktesias of Knidos and Ailianus the sophist.